Analysis of topicality in classroom discourse: topic switch and topic drift in conversations in EFL contexts - Fernández Agoero, María (Estudios Ingleses de la Universidad Complutense, 2003)
This study is meant to contribute to the study of topic coherence in interaction: I will examine conversations in English between native English speakers and Spanish speakers in the context of classroom discourse and EEL teaching, and analyse how participants contribute to maintain and change the topic. In particular, topic shift is analysed in two semi-spontaneous conversations where Spanish speakers with different degrees of proficiency in English are involved. The expected outcome is that in the conversation with the lower-level student, there will be (i) a wider range and higher number of strategies used by the native English interlocutor to keep the conversation going; (ii) more drastic clear-cut changes of topic (or switches) and (iii) more topic movement in general. Results prove that this is not the case in (i) and (ii) but the initial hypothesis is validated for (iii). This last finding is corroborated by the quantitative analysis of six more interviews recorded under the same circumstances. Finally, I draw conclusions and suggest possible questions for further research.
Keywords: Topicality; Topic movement; Classroom discourse; English as a foreign language